2019
DOI: 10.1016/j.addbeh.2018.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress and gambling related cognitions: Analyses in inpatient and online samples

Abstract: Gambling disorder (GD) is associated with a range of psychiatric comorbidities. One comorbidity of particular interest is post-traumatic stress disorder (PTSD). Individuals with GD report much higher rates of PTSD than the general population, and individuals with this comorbidity (with both PTSD and GD) often report much greater distress and impairment in daily life in comparison to individuals with GD alone. Despite these associations, little is known about the specific ways in which PTSD and GD might influen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…10 Moreover, other work has shown that among both recreational and disordered gamblers, PTSS/PTSD are associated with more cognitive distortions around gambling and problematic beliefs about gambling, particularly the belief that gambling will enhance mood or positive affect. 14 Collectively, these findings indicate that PTSS/PTSD are associated with unique motivations for and beliefs about gambling behaviors, which also suggests that individuals experiencing PTSS/PTSD might be particularly vulnerable to specific gambling related triggers or situations.…”
Section: Substance Abuse: Research and Treatmentmentioning
confidence: 81%
See 1 more Smart Citation
“…10 Moreover, other work has shown that among both recreational and disordered gamblers, PTSS/PTSD are associated with more cognitive distortions around gambling and problematic beliefs about gambling, particularly the belief that gambling will enhance mood or positive affect. 14 Collectively, these findings indicate that PTSS/PTSD are associated with unique motivations for and beliefs about gambling behaviors, which also suggests that individuals experiencing PTSS/PTSD might be particularly vulnerable to specific gambling related triggers or situations.…”
Section: Substance Abuse: Research and Treatmentmentioning
confidence: 81%
“…To address the above research directions, we analyzed data from two samples that have been described in previously published works. 10,14 All research was approved by the Institutional Review Boards at the respective institutions at which they were conducted (Sample 1 = Bowling Green State University; Sample 2 = Cleveland Veteran's Affairs Medical Center and Bowling Green State University).…”
Section: Methodsmentioning
confidence: 99%
“…Materials and Methods To address the above research directions, we analyzed data from two samples that have been described in previously published works. 10,14 All research was approved by the Institutional Review Boards at the respective institutions at which they were conducted (Sample 1 = Bowling Green State University; Sample 2 = Cleveland Veteran's Affairs Medical Center and Bowling Green State University).…”
Section: Gambling Situationsmentioning
confidence: 99%
“…Full details about this screening process have been published elsewhere. 10,14 Due to the above screening process, the final sample size was 589 adults (inclusion rate = 86%; 43% men, Mage = 36.1, SD = 11.0). Participants were primarily White/Caucasian (76%), African-American/Black (11%), Native American/American Indian (2%), Asian/Pacific Islander (9%), Hispanic/Latino (8%), and other/prefer-not-to-say (2%).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Estimated rates suggest that the lifetime prevalence of GD in U.S. military veterans is 2%, while lifetime estimates of problem gambling have been reported to be as high as 11% (Steenbergh et al, 2008;Westermeyer et al, 2013;Whiting et al, 2016). Among treatment-seeking Veterans Affairs (VA) patients diagnosed with GD, research has also revealed frequent co-occurrences of substance use disorders and PTSD (Grubbs et al, 2018;Grubbs et al, 2019;Ronzitti et al, 2019;Shirk et al, 2018). Unfortunately, gambling research conducted on U.S. veterans is scarce, despite growing evidence that this group may be particularly vulnerable to developing gambling problems (Etuk et al, 2020).…”
Section: Introductionmentioning
confidence: 99%